Analysis of risks factors associated with construction projects in urban wetlands ecosystem. Issue 2 (17th February 2023) - Asumadu, G.; Quaigrain, R.; Owusu-Manu, D.; Edwards, D.J.; Oduro-Ofori, E.; Kukah, ASK.; Nsafoah, S.K.
ABSTRACT: Within some developing countries, wetlands have long been regarded as dumping grounds. However, there has been a gradual paradigm shift in societal attitudes towards recognising their importance as landscape features that provide benefits for humans and wildlife. Unfortunately, construction activities have continually plagued their existence. Therefore, this present research examines the risks factors associated with construction projects in wetlands ecosystem, using Ghana as a case study. A quantitative research strategy leaning towards the positivist paradigm was adopted. A structured survey was developed to collect data from key stakeholders. Purposive sampling was employed to recruit construction experts in the Kumasi Metropolis, with a total of 78 experts agreeing to participate. Relative Importance Index (RII), Mean Score Ranking and a One-Sample T-Test were used to analyse primary data collected. The findings revealed that the key driving forces spurring construction projects in wetlands were rapid urbanisation; high rate of migration; and scarcity of land for development. Critical risks factors associated with construction projects in wetlands were identified as cost overruns; exploitation of biological resources; and water pollution. Finally, the findings also showed that the most critical detrimental effects of construction projects in wetlands were the destruction of aquatic and terrestrial lives; loss of flood control capability; and deterioration of wetland water quality. The study recommends the protection and conservation of wetlands environments through systematized enactment and enforcement of environmental protection regulations by government and non-governmental institutions. This would ensure the preservation of important biodiversity and aid with pollution control and flood protection.